2019
DOI: 10.1186/s12875-019-0911-1
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and barriers towards conducting research amongst primary care physicians in Bahrain: a cross-sectional study

Abstract: BackgroundResearch in primary care is essential for disease diagnosis, management and prevention in relation to the individuals, families and the community. This research aims to study the attitude of primary care physicians towards conducting research in Bahrain and to identify the main barriers encountered during research.MethodsA cross-sectional study was conducted amongst 200 randomly selected primary care physicians registered in Ministry of Health affiliated primary healthcare centers in Bahrain. A self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 9 publications
4
17
2
Order By: Relevance
“…However, the ndings from other previous studies indicate a low self -assessed research capacity among nurses (30,31) and a need for training in research methods among nurses and other HCPs (30,32,33). In alignment with our study ndings, lack of research resources like time and funding were found to be the most commonly perceived barriers to undertaking research among practitioners in the UK ,USA and Bahrain (28,29,34), increased paper work and disruption to work ows (34) Overall, the perceived importance on the speci c tasks was positively correlated with the overall perceived performance of tasks related to RMNH services. Similarly, ndings of a study in South Africa indicated that, the more comprehensively professional nurses were trained, the more competent they felt, and they expressed more negativity towards their work if they perceived they were inadequately trained (36).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…However, the ndings from other previous studies indicate a low self -assessed research capacity among nurses (30,31) and a need for training in research methods among nurses and other HCPs (30,32,33). In alignment with our study ndings, lack of research resources like time and funding were found to be the most commonly perceived barriers to undertaking research among practitioners in the UK ,USA and Bahrain (28,29,34), increased paper work and disruption to work ows (34) Overall, the perceived importance on the speci c tasks was positively correlated with the overall perceived performance of tasks related to RMNH services. Similarly, ndings of a study in South Africa indicated that, the more comprehensively professional nurses were trained, the more competent they felt, and they expressed more negativity towards their work if they perceived they were inadequately trained (36).…”
Section: Resultssupporting
confidence: 85%
“…time, money, information, equipment) and identifying research needs and designing locally relevant research were among the topics that received the highest ratings. This ndings contradicts a common stereotype on lack of interest for research among clinicians reported in United Kingdom and Bahrain (28,29). However, the ndings from other previous studies indicate a low self -assessed research capacity among nurses (30,31) and a need for training in research methods among nurses and other HCPs (30,32,33).…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…The participants in this study had a remarkably positive attitude for CTs with a mean score of 7.07±1.82 which is comparable with studies done elsewhere [21]. It is evident from the study that the participants were personally motivated to conduct CTs.…”
Section: Discussionsupporting
confidence: 85%
“…In general, the barriers focused on logistics, research infrastructure, human resources capacity, support and funding, culture, and political economy. Indeed, studies within and outside the region noted that logistical difficulties like insufficient time allotted to research prevent physicians from engaging in research activities [ 7 20 21 ]. Further, establishing strong research infrastructure, including data production and cancer registration, is essential for developing national and regional cancer control plans.…”
Section: Discussionmentioning
confidence: 99%